Teachers and trainers in vocational training - Cordova, Pedro (CEDEFOP, 1998)
Contents: vol.1.Germany, Spain, France and the United Kingdom - vol.2.Italy, Ireland and Portugal - vol.3.Austria, Belgium, Greece, Luxembourg and the Netherlands - vol.4.Denmark, Finland, Iceland, Norway and Sweden